Gelatin Production from Skin of Chicken Leg using A Variety of Naoh Concentration - Rety Setyawaty; May Triliandari (Faculty of Animal Science Universitas Brawijaya, 2018)
Gelatin is a type of protein that is extracted from collagen of skin, bone, or ligament (animal connective tissue) tissue. Cow bone, cowhide and pig skin are the materials commonly used to obtain gelatin. The purpose of this research was to determine the difference of NaOH concentration as soaking agent on gelatin making from skin of chicken leg (Gallus gallus domesticus) for 72 hours of soaking. Fresh skin of chicken leg weighing 250 g were immersed in NaOH solution with concentrations of 1%, 1.5%, and 3% for 72 hours, then extracted using n-hexane solution: alcohols in a ratio of 1: 3 and dried to obtain gelatin. The resulting gelatin is then analyzed for physicochemical characteristics such as sensory, yield, pH test, and water content test. The results of this study, mentioned that the concentration of 1% NaOH solution produces gelatin under average of yield of 6 g, neutral pH and water content of 11%. The concentration of 1.5% NaOH solution produces gelatin under average of yield 8 g, pH 7 and water content of 13%. The concentration of 3%NaOH solution produces gelatin under average of yield 4.144 g, pH 7 and water content of 7.11%. Based on the result, it can be concluded that a good solution of NaOH to get high yield under a concentration of 1.5% solution. The gelatin obtained under 1.5% solution in accordance with the standard gelatin. The characteristics of standard gelatin are colorless to yellow, odorless, tasteless, pH 7 (neutral), and moisture content below 16%.